Energy communities of repair in remote infrastructures: a study of Puerto Edén in the Chilean Patagonia - Baigorrotegui, Gloria; González, Dominique; Gumucio, Cristian Parker (Sustainability in Debate, 2023)
Energy communities contribute to the justice of energy transition efforts to enhance the democratisation of contemporary energy policies. We ask what kind of circumstances and practices facilitate the continuity of energy access in remote communities with lagging infrastructures. To answer this question, we propose an approach to researching energy communities of repair based on a study of Puerto Edén, a remote island in the Chilean Patagonia. Since 2020, research has been carried out in this locality using an ethnographic and interactive methodology from a Science and Technology Studies (STS) perspective through systematic fieldwork. The results demonstrate the challenges these communities face as they address deficiencies in governance, providing provisional and definitive solutions. Abandonment of renewable infrastructure could be avoided if historic energy repair communities in remote locations are identified and involved in just energy transition programs.